Perceived family support status and associated factors among people with hypertension in Nekemte City public hospitals, Western Ethiopia - Zewude Mulatu Geleta; Dereje Chala Diriba; Desalegn Emana Jabana (PLoS ONE, 2025)
Background Though previous studies reported the advantages of family in treating people with hypertension, evidence indicates that family support among people with hypertension was poor. To the best of the researchers’ knowledge, no study examined the status of perceived family support and associated factors among people with hypertension in Ethiopia. Therefore, this study assessed perceived family support status and associated factors among people with hypertension in Nekemte City public hospitals, Western Ethiopia, Methods A hospital based cross sectional study on 422 selected adults with hypertension was conducted in public hospitals in Nekemte from June to August 2023. A systemic random sampling technique was used to select eligible participants. Bivariate and multivariable logistic regression analyses were carried out, and variables with a p-value < 0.25 in the bivariate analysis were included in the multivariable analysis to identify factors associated with perceived family support at a P-value < 0.05. Results Two hundred ninety two (70.4%), 95% CI (65.7%, 74.7%), of people with hypertension reported perceived strong family support. Having a family history of hypertension [AOR = 3.6, 95% CI (1.266, 10.34)], involvement of families during patient education on HTN [AOR = 3.305, 95% CI (2.306, 8.363)], and good interaction with family [AOR = 2.45, 95% CI (1.002, 5.32)] were positively associated with perceived family support. Whereas, patients who are poorly knowledgeable about hypertension [AOR = 0.3, 95% CI (0.001, 0.542)] were negatively associated with perceived family support, Conclusion Two hundred ninety two people with hypertension reported perceived strong family support. Having a family history of hypertension, involvement of families during patient education on hypertension, and patients’ interaction with family were positively statistically associated with perceived family support and patients who are poorly knowledgeable about hypertension were negatively associated with perceived family support. Hospitals, along with other stakeholders, should strengthen family support by involving families in health education in line with hypertension patients’ lifestyles.